Speech and language in autism spectrum disorder: a view through the lens of behavior and brain imaging. (April 2013) - Mody, Maria; Manoach, Dara S; Guenther, Frank H; Kenet, Tal; Bruno, Katelyn A; McDougle, Christopher J; Stigler, Kimberly Ann
SUMMARY Numerous studies have examined the brain bases of autism; few, however, have specifically examined the neurobiology of speech and language impairments in children and adults on the spectrum, especially those characterized as low functioning or minimally verbal, due to compliance issues. With exciting new advances in the development of paradigms and tools, and the ability to image children at risk for autism as young as 6 months of age, functional neuroimaging (EEG, magnetoencephalography and functional MRI) holds tremendous promise. Findings of reduced activation and structural and functional connectivity in the language network, together with deficits in social reciprocity and motivation, and a preference for visual over verbal information, appear to be carving out a neurobiological profile for the impaired social–communication brain in autism.